Method for preparing oxygen-containing chemicals by synergistic catalytic oxidation of lignocellulose and methanol
Through synergistic catalytic oxidation wood cellulose and methanol, the use of acid and V-Beta nano-molecular sieving catalysts can solve the problem of biomass preparation of methamphetamine catalyst synthesis, high cost and low yield, and achieve high efficiency and low yield. Cost, environmentally friendly, and formaldehyde -containing chemicals containing oxye chemicals.
Patent Information
- Application Number
- CN202411500025.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When the prior art uses biomass to prepare formic acid, the catalyst synthesis is difficult, the cost is high, and the yield and selectivity are low, making it difficult to be suitable for large-scale industrial applications.
The method of synergistic catalytic oxidation wood cellulose and methanol, using acid and V-BETA nano-molecular sieve as a catalyst, oxygen or air as oxidant, at a lower temperature and time, high-selective oxidation to generate dimeric acid, formaldehyde and other oxygenochemics containing oxygencoustis content Products, and methamphetamine and formaldehyde are generated through esterization and synthesis reactions.
Achieving efficiently preparing oxygen -containing chemicals such as titron and formaldehyde at lower temperature and time, improved the stability and recycling efficiency of catalysts, reduced production costs and environmental pollution, and conforming to the development trend of green chemistry.
Smart Images

Figure CN119371306A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic synthesis, and particularly relates to a method for preparing oxygen-containing chemicals by synergistic catalytic oxidation of lignocellulose and methanol. Background Art
[0002] Oxygen-containing chemicals are important chemical raw materials, such as formic acid, methyl formate, methylal, etc. Formic acid, as an organic acid, has been widely used in medicine, agriculture, industry, leather, textile, printing and dyeing, food, rubber and other fields. In addition, formic acid can also be used as an acid electrolyte for fuel cells, as well as a carrier for the storage and transportation of hydrogen. Methyl formate is an important organic synthesis intermediate and has been widely used in the production of formic acid, various formamides and other chemicals. It can also be used as an organic synthesis raw material, a solvent for cellulose acetate, a fungicide, a fumigant, an insecticide, a grain and tobacco treatment agent, etc. Methylal, also known as dimethoxymethane, can be used as an organic synthesis intermediate, a solvent, etc. It has the characteristics of low toxicity, good solubility and environmental friendliness. It is widely used in paints, coatings, rubber, leather, electronics, industrial cleaning, aerosols and other fields. High-purity methylal can also be used in the production of cosmetics and medicines, and can also be used as a hydrogen storage material.
[0003] Today, the consumption of fossil energy has led to a large amount of greenhouse gas emissions, causing increasingly serious environmental and climate problems. Therefore, it is crucial to seek sustainable alternatives for the production of chemicals and fuels. Lignocellulose is the most promising: as a biomass resource, it is mainly composed of cellulose, hemicellulose and lignin, and has the advantages of carbon neutrality, economy and easy availability. The efficient use of lignocellulose helps reduce dependence on fossil raw materials and promote the sustainable development of today's society, and is a hot topic of current research.
[0004] At present, there have been some reports on the use of biomass to prepare formic acid. For example, a Chinese patent (application number 202211358091.7) discloses a method for preparing formic acid by catalyzing oxygen oxidation of biomass carbohydrates using a vanadium-containing heteropoly acid as a catalyst. Although this method has a high formic acid yield, the catalyst synthesis is difficult and costly, and is not suitable for large-scale industrial applications. A Chinese patent (application number 202211478836.3) discloses a method for preparing formic acid from biomass using CuO hydrothermal oxidation, which involves a low-corrosive base-catalyzed oxidation process, but the yield and selectivity of the main product formic acid are very low. A Chinese patent (application number 202211294279.7) discloses a method for catalyzing the preparation of formic acid from carbohydrate biomass at near room temperature. The method has mild conditions and the catalyst is easy to regenerate, but there is also a problem of low yield of the main product formic acid. There are also reports in journal articles on the catalytic oxidation of biomass to prepare oxygen-containing chemicals. Liu et al. (Liu Q, Zhou D, Li Z, et al. Efficient and Bio-inspired Conversion of Cellulose to Formic Acid Catalyzed by Metalloporphyrins in Alkaline Solution. Chinese Journal of Chemical, 2017 (7): 1063-1068.) used cellulose as raw material, metalloporphyrin mimicking cytochrome P450 as catalyst, NaOH solution as solvent, and oxygen as oxidant. At 150°C, the final yield of formic acid was 63.7%. However, since the reaction medium was NaOH solution, the generated product needed to be acidified to obtain formic acid, which greatly increased the cost.
[0005] In industrial production, silver catalysts are usually used to catalyze the reaction of methanol into formaldehyde. This conversion reaction is carried out under certain temperature and pressure conditions, usually at a high temperature of 600-650°C and a pressure of 0.3-0.5MPa, with high reaction temperature and energy consumption. Regarding methylal, the most mature technology used in industrial production is the alcohol-aldehyde condensation method. Methanol and formaldehyde aqueous solution undergo acetalization reaction in a tubular reactor to generate methylal. Each ton of methylal product requires about 1.3 tons of formaldehyde aqueous solution and about 1.1 tons of industrial-grade methanol raw materials. Methanol and formaldehyde aqueous solution are used as raw materials in production, and inorganic acids (such as sulfuric acid, hydrochloric acid), Lewis acids (such as aluminum chloride, ferric chloride, etc.) and heteropoly acids (such as silicotungstic acid, phosphotungstic acid) are used as catalysts. Summary of the invention
[0006] The invention discloses a method for preparing oxygen-containing chemicals by synergistic catalytic oxidation of lignocellulose and methanol. The method uses lignocellulose as a raw material, water and methanol as solvents, acid and V-Beta nanomolecular sieve as catalysts, and oxygen or air as an oxidant. At a relatively low temperature and time, the lignocellulose and methanol are highly selectively oxidized into oxygen-containing chemicals such as formic acid and formaldehyde. Part of the formic acid generated by oxidation reacts with methanol through an esterification reaction to obtain methyl formate, and part of the formaldehyde generated by oxidation reacts with methanol to obtain methylal.
[0007] The present invention prepares V-Beta nano molecular sieve catalyst by direct synthesis method, introduces vanadium source in the molecular sieve synthesis process, makes vanadium grow evenly in the molecular sieve framework. This growth mode causes vanadium to exist mainly in three forms: monomer vanadium oxygen species, oligomeric vanadium oxygen species, and crystalline V2O5. Among them, the combination of monomer and oligomeric vanadium species with Beta nano molecular sieve provides active center for it, while crystalline V2O5 is dispersed in the cage structure of molecular sieve, further enhancing the catalytic effect. The design of this catalyst not only improves the hydrothermal stability of molecular sieve, but also increases the stability of vanadium by combining with molecular sieve, simplifies the recovery process, and reduces environmental pollution. In addition, the existence form of vanadium plays a vital role in the catalytic reaction, and the vanadium species combined with molecular sieve is the key active site of the catalytic reaction. This molecular sieve catalyst shows remarkable effects in the synergistic catalytic oxidation reaction of biomass and methanol. It not only improves the selectivity of formic acid, but also effectively inhibits the formation of by-product CO2. At the same time, it promotes the dissolution of oxygen in water, increases the catalytic oxidation rate, reduces the reaction temperature and time, and realizes the catalytic oxidation of methanol to produce formaldehyde and methylal at low temperature.
[0008] The present invention also relates to a method for recycling V-Beta nanomolecular sieve catalysts. After the coordinated catalytic oxidation process of lignocellulose and methanol is completed, the V-Beta nanomolecular sieve catalyst can be effectively recovered by calcining the filter residue. This step not only simplifies the recovery process of the catalyst, but also ensures its reuse in subsequent reactions, further reducing production costs and reducing environmental pollution. Through this innovative recovery technology, the service life of the V-Beta nanomolecular sieve catalyst is extended, while improving the economic benefits and environmental sustainability of the entire catalytic process.
[0009] The present invention is achieved through the following technical solutions:
[0010] A method for preparing oxygen-containing chemicals by synergistic catalytic oxidation of lignocellulose and methanol comprises the following steps:
[0011] Adding lignocellulose raw materials, methanol, water, inorganic acid, and V-Beta nanomolecular sieve into a reactor, charging a certain amount of oxygen or air, stirring and reacting at a certain temperature for a certain time, cooling to room temperature after the reaction, filtering the product in the reactor, collecting the filter residue and the filtrate respectively, and recovering the V-Beta nanomolecular sieve catalyst by calcining the filter residue;
[0012] The preparation steps of the V-Beta nanomolecular sieve are as follows:
[0013] Step 1: Dissolve ammonium metavanadate in water and mix it evenly with white carbon black, and dry it at 60-80°C for 5-12 hours. The mass ratio is white carbon black: ammonium metavanadate: water = 1: 0.1-0.3: 0.8-1.2;
[0014] Step 2: Mix aluminum oxide and tetraethylammonium hydroxide solution, and stir magnetically for 30 minutes at a speed of 500 r / min to completely dissolve the aluminum oxide, with a mass ratio of aluminum oxide:tetraethylammonium hydroxide solution = 1:20-50;
[0015] Step 3: Add the dried white carbon black to the mixed solution, mix well, and dry at 70° C. for 6-8 hours to obtain a mixture, wherein the mass ratio of aluminum oxide to white carbon black is 1:25-50;
[0016] Step 4: Grind the dried mixture in the above step 3 and transfer it into an open glass vessel, then transfer it into the lining of a hydrothermal reactor, add 4 to 20 mL of deionized water into the lining of the hydrothermal reactor, and prevent water outside the glass vessel from entering the glass vessel; adjust the hydrothermal reactor to 160 to 180° C. under steam-assisted conditions, and crystallize the mixture for 8 to 20 hours to obtain a crystalline product;
[0017] Step 5: After the crystallized product is naturally cooled to room temperature, it is washed twice and dried, and calcined at 500-600° C. in an air atmosphere for 12 hours to obtain a V-Beta nanomolecular sieve with high crystallinity;
[0018] Furthermore, the types of lignocellulose raw materials include corn straw, wheat straw, bean straw, corn cob, sugarcane bagasse, sawdust, and bamboo;
[0019] Furthermore, the inorganic acid catalyst includes phosphoric acid, hydrochloric acid, sulfuric acid, and nitric acid;
[0020] Furthermore, the mass ratio of the lignocellulose raw material to methanol is 1:1 to 1:10;
[0021] Furthermore, the mass ratio of the lignocellulose raw material to water is 1:5 to 1:25;
[0022] Furthermore, the inorganic acid and V-Beta nanomolecular sieve catalyst are used in the following ratios: the mass ratio of lignocellulose raw material to inorganic acid is 1:0.1 to 1:0.8, and the mass ratio of lignocellulose raw material to V-Beta nanomolecular sieve is 1:0.02 to 1:0.2.
[0023] Furthermore, the reaction parameters are: reaction temperature 100°C to 160°C, reaction time 0.5h to 3h, reaction pressure 1.0MPa to 5MPa.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The invention discloses a method for preparing oxygen-containing chemicals by synergistic catalytic oxidation of lignocellulose and methanol. The method uses lignocellulose as a raw material, water and methanol as solvents, acid and V-Beta nanomolecular sieve as catalysts, and oxygen or air as an oxidant. At a relatively low temperature and time, the lignocellulose raw material and methanol are highly selectively oxidized into oxygen-containing chemicals such as formic acid and formaldehyde. Part of the formic acid generated by oxidation reacts with methanol through an esterification reaction to obtain methyl formate, and part of the formaldehyde generated by oxidation reacts with methanol to obtain methylal. The participation of methanol increases the solubility of oxygen in water, improves the catalytic oxidation rate of V-Beta nanomolecular sieve, reduces the reaction temperature, reduces the reaction time, and realizes a positive synergistic mechanism of catalytic oxidation of biomass and methanol under the participation of V-Beta nanomolecular sieve catalyst. The design of V-Beta nanomolecular sieve catalyst makes the utilization of vanadium more efficient and reduces the possible pollution of heavy metals to the environment. This environmentally friendly process design not only conforms to the current development trend of green chemistry, but also provides a new solution for the sustainable development of the chemical industry.
[0026] The recycling strategy of V-Beta nano-molecular sieve catalyst proposed in the present invention. By recovering the catalyst by calcining the filter residue, we not only simplify the recovery process, but also ensure that the activity of the catalyst is maintained, so that it can be reused in multiple reaction cycles. This recycling strategy significantly reduces production costs and reduces the burden of waste catalysts on the environment.
[0027] The present invention opens up a new path for the efficient synthesis of oxygen-containing chemicals by synergistically catalytically oxidizing lignocellulose and methanol. Under the action of the V-Beta nanomolecular sieve catalyst, lignocellulose raw materials and methanol can be highly selectively converted into valuable chemicals such as formic acid and formaldehyde at a lower temperature and time. This process not only improves the conversion rate of raw materials, but also further increases the diversity and value of products through esterification and condensation reactions. This innovative synthesis route not only improves the utilization efficiency of raw materials, but also provides new ideas for the diversification of chemical raw materials and the high value of chemicals. Through this method, we can produce a wider variety of chemicals with fewer steps and lower energy consumption, which is of great significance in the chemical industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 A flow chart of a method for preparing oxygen-containing chemicals by synergistic catalytic oxidation of lignocellulose and methanol. DETAILED DESCRIPTION
[0029] The present invention is described below by specific examples, so as to facilitate understanding of the law and optimal conditions of cooperative catalytic oxidation. It should be pointed out that for those skilled in the art, some changes and improvements may be made without violating the concept of the present invention. These changes and improvements should be included in the protection scope of the present invention.
[0030] Example 1
[0031] In this example, 2g corn stalks and 15ml methanol are used as raw materials, 30mL water is used as solvent, 0.5g acid and 0.1g V-Beta nano molecular sieve catalyst are placed in a high temperature and high pressure reactor with stirring, oxygen is filled to a pressure of 2MPa, and the reaction is stirred at 130°C for 2h. After the reaction is completed, it is cooled to room temperature, the product in the reactor is taken out and weighed, and then filtered and separated, and the filter residue and filtrate are collected respectively. The filtrate is stored in a sealed bottle, the filter residue is dried and weighed, and the filter residue is calcined to recover the V-Beta nano molecular sieve catalyst. The filtrate is quantitatively analyzed by gas chromatograph. The gas chromatograph used is Shimadzu GC-2030A, the detector is BID detector, the chromatographic column is Agilent DB-624, and the carrier gas is helium.
[0032] The preparation steps of V-Beta nano molecular sieve catalyst are as follows:
[0033] 0.35g of ammonium metavanadate was dissolved in water and mixed evenly with 2g of white carbon black, and dried at 75℃ for 6h. 0.068g of aluminum oxide was mixed with 3.1g of tetraethylammonium hydroxide solution, and the magnetic stirring speed was 30min and the speed was 500r / min to completely dissolve the aluminum oxide. The dried white carbon black was added to the above mixed solution, mixed evenly, and dried at 70℃ for 7h to obtain a mixture. The above dried mixture was ground and moved into an open glass vessel, and then transferred to the lining of the hydrothermal reactor. 5mL of deionized water was added to the lining of the hydrothermal reactor, and water outside the glass vessel was prevented from entering the glass vessel; under steam-assisted conditions, the hydrothermal reactor was adjusted to 165℃, and the mixture was crystallized. The crystallized product was obtained after crystallization for 12h. After the crystallized product was naturally cooled to room temperature, it was washed twice and dried, and calcined at 550℃ in air atmosphere for 12h to obtain a high crystallinity V-Beta nanomolecular sieve.
[0034] The filtrate was subjected to quantitative product analysis by gas chromatograph, the gas chromatograph used was Shimadzu GC-2030A, the detector was BID detector, the chromatographic column was Agilent DB-624, and the carrier gas was helium. The results showed that the corn stalk conversion rate was 82.6%, calculated based on the initial stalk mass (the solvent methanol participated in the reaction so the cumulative yield was higher than 100%), the formic acid mass yield was 54%, the methyl formate mass yield was 56.5%, the methylal mass yield was 10%, and the formaldehyde yield was 6%.
[0035] The element analysis of the V-Beta nano-molecular sieve catalyst was performed using ICPMS-2030 from Shimadzu Corporation of Japan, and the results showed 81.5% silicon, 13.3% aluminum, and 5.2% vanadium.
[0036] Example 2
[0037] In this example, 2g corn stalks and 20mL methanol were used as raw materials, 25mL water was used as solvent, 0.5g acid and 0.1g V-Beta nano molecular sieve catalyst were placed in a high temperature and high pressure reactor with stirring, oxygen was filled to a pressure of 2MPa, and the reaction was stirred at 130°C for 2h. After the reaction was completed, the product in the reactor was cooled to room temperature, and the mass was taken out, and then filtered and separated. The filter residue and filtrate were collected respectively, and the filtrate was stored in a sealed bottle. The filter residue was dried and weighed, and the filter residue was calcined to recover the V-Beta nano molecular sieve catalyst. The results showed that the corn stalk conversion rate was 84.8%, and the mass yield of formic acid was 49%, the mass yield of methyl formate was 62%, the yield of methylal was 14%, and the yield of formaldehyde was 10% based on the initial stalk mass.
[0038] The preparation of V-Beta nano molecular sieve catalyst is described in Example 1.
[0039] Example 3
[0040] In this example, 2g corn stalks and 22.5mL methanol were used as raw materials, 22.5mL water was used as solvent, 0.5g acid and 0.1g V-Beta nano molecular sieve were used as catalysts, placed in a high temperature and high pressure reactor with stirring, oxygen was charged to a pressure of 2MPa, stirred and reacted for 2h at 130℃, cooled to room temperature after the reaction, the product in the reactor was taken out and weighed, and then filtered and separated, the filter residue and filtrate were collected respectively, the filtrate was stored in a sealed bottle, the filter residue was dried and weighed, the filter residue was calcined, and the V-Beta nano molecular sieve catalyst was recovered. The results showed that the corn stalk conversion rate was 84.2%, and the mass yield of formic acid was 45%, the mass yield of methyl formate was 71%, the yield of methylal was 23.5%, and the yield of formaldehyde was 15% based on the initial stalk mass.
[0041] The preparation of V-Beta nano molecular sieve catalyst is described in Example 1.
[0042] Example 4
[0043] In this example, 2g corn stalks and 25mL methanol were used as raw materials, 20mL water was used as solvent, 0.5g acid and 0.1g V-Beta nano molecular sieve were used as catalysts, placed in a high temperature and high pressure reactor with stirring, oxygen was charged to a pressure of 2MPa, stirred and reacted for 2h at 130℃, cooled to room temperature after the reaction, the product in the reactor was taken out and weighed, and then filtered and separated, the filter residue and filtrate were collected respectively, the filtrate was stored in a sealed bottle, the filter residue was dried and weighed, the filter residue was calcined, and the V-Beta nano molecular sieve catalyst was recovered. The results showed that the corn stalk conversion rate was 84.1%, and the mass yield of formic acid was 41.5%, the mass yield of methyl formate was 72%, the yield of methylal was 28%, and the yield of formaldehyde was 16.2% based on the initial stalk mass.
[0044] The preparation of V-Beta nano molecular sieve catalyst is described in Example 1.
[0045] Example 5
[0046] In this example, 2g corn stalks and 30mL methanol were used as raw materials, 15mL water was used as solvent, 0.5g acid and 0.1g V-Beta nano molecular sieve were used as catalysts, placed in a high temperature and high pressure reactor with stirring, oxygen was charged to a pressure of 2MPa, stirred and reacted at 130℃ for 2h, cooled to room temperature after the reaction, the product in the reactor was weighed, filtered and separated, the filter residue and filtrate were collected respectively, the filtrate was stored in a sealed bottle, the filter residue was dried and weighed, the filter residue was calcined, and the V-Beta nano molecular sieve catalyst was recovered. The results showed that the corn stalk conversion rate was 84%, and the mass yield of formic acid was 40%, the mass yield of methyl formate was 72.4%, the yield of methylal was 33%, and the yield of formaldehyde was 16.8% based on the initial stalk mass.
[0047] Example 6
[0048] In this example, 2g corn stalks and 22.5mL methanol were used as raw materials, 22.5mL water was used as solvent, 0.5g acid and 0.1g V-Beta nano molecular sieve were used as catalysts, placed in a reactor, filled with oxygen 2MPa, stirred and reacted for 0.5h at 130℃, cooled to room temperature after the reaction, weighed the product in the reactor, filtered and separated, and the filter residue and filtrate were collected respectively. The filtrate was stored in a sealed bottle, and the filter residue was dried and weighed. The results showed that the conversion rate of corn stalks was 73.4%, and the mass yield of formic acid was 37%, the mass yield of methyl formate was 47.5%, the yield of methylal was 15%, and the yield of formaldehyde was 6% based on the initial stalk mass.
[0049] The preparation of V-Beta nano molecular sieve catalyst is described in Example 1.
[0050] Example 7
[0051] In this example, 2g corn stalks and 22.5mL methanol were used as raw materials, 22.5mL water was used as solvent, 0.5g acid and 0.1g V-Beta nano molecular sieve were used as catalysts, placed in a reactor, filled with oxygen 2MPa, stirred and reacted for 1h at 130℃, cooled to room temperature after the reaction, weighed the product in the reactor, filtered and separated, and the filter residue and filtrate were collected respectively. The filtrate was stored in a sealed bottle, the filter residue was dried and weighed, the filter residue was calcined, and the V-Beta nano molecular sieve catalyst was recovered. The results showed that the corn stalk conversion rate was 78.6%, and the mass yield of formic acid was 40.5%, the mass yield of methyl formate was 51%, the yield of methylal was 17%, and the yield of formaldehyde was 10.8% based on the initial stalk mass.
[0052] The preparation of V-Beta nano molecular sieve catalyst is described in Example 1.
[0053] Example 8
[0054] In this example, 2g corn stalks and 22.5mL methanol were used as raw materials, 22.5mL water was used as solvent, 0.5g acid and 0.1g V-Beta nano molecular sieve were used as catalysts, placed in a high temperature and high pressure reactor with stirring, oxygen was charged to a pressure of 2MPa, and stirred for 1.5h at 130℃. After the reaction, it was cooled to room temperature, the product in the reactor was weighed, filtered and separated, and the filter residue and filtrate were collected respectively. The filtrate was stored in a sealed bottle, the filter residue was dried and weighed, the filter residue was calcined, and the V-Beta nano molecular sieve catalyst was recovered. The results showed that the corn stalk conversion rate was 81.8%, and the mass yield of formic acid was 46%, the mass yield of methyl formate was 58.5%, the yield of methylal was 20.5%, and the yield of formaldehyde was 13.9% based on the initial stalk mass.
[0055] The preparation of V-Beta nano molecular sieve catalyst is described in Example 1.
[0056] Example 9
[0057] In this example, 2g corn stalks and 22.5mL methanol were used as raw materials, 22.5mL water was used as solvent, 0.5g acid and 0.1g V-Beta nano molecular sieve were used as catalysts, placed in a reactor, filled with oxygen 2MPa, stirred and reacted for 2.5h at 130℃, cooled to room temperature after the reaction, weighed the product in the reactor, filtered and separated, and the filter residue and filtrate were collected respectively. The filtrate was stored in a sealed bottle, and the filter residue was dried and weighed. The results showed that the conversion rate of corn stalks was 86.4%, and the mass yield of formic acid was 37.5%, the mass yield of methyl formate was 69%, the yield of methylal was 20.5%, and the yield of formaldehyde was 13.2% based on the initial stalk mass.
[0058] The preparation of V-Beta nano molecular sieve catalyst is described in Example 1.
[0059] Example 10
[0060] In this example, 2g corn stalks and 22.5mL methanol were used as raw materials, 22.5mL water was used as solvent, 0.5g acid and 0.1g V-Beta nano molecular sieve were used as catalysts, placed in a high temperature and high pressure reactor with stirring, oxygen was charged to a pressure of 2MPa, stirred and reacted for 2h at 135℃, cooled to room temperature after the reaction, the product in the reactor was weighed, filtered and separated, the filter residue and filtrate were collected respectively, the filtrate was stored in a sealed bottle, the filter residue was dried and weighed, the filter residue was calcined, and the V-Beta nano molecular sieve catalyst was recovered. The results showed that the corn stalk conversion rate was 71.4%, and the mass yield of formic acid was 13.5%, the mass yield of methyl formate was 56.5%, and the yield of methylal was 17.5% based on the initial stalk mass.
[0061] The preparation of V-Beta nano molecular sieve catalyst is described in Example 1.
[0062] Embodiment 11
[0063] In this example, 2g corn stalks and 22.5mL methanol were used as raw materials, 22.5mL water was used as solvent, 0.5g acid and 0.1g V-Beta nano molecular sieve were used as catalysts, placed in a high temperature and high pressure reactor with stirring, oxygen was charged to a pressure of 2MPa, stirred and reacted at 140℃ for 2h, cooled to room temperature after the reaction, the product in the reactor was weighed, filtered and separated, the filter residue and filtrate were collected respectively, the filtrate was stored in a sealed bottle, the filter residue was dried and weighed, the filter residue was calcined, and the V-Beta nano molecular sieve catalyst was recovered. The results showed that the corn stalk conversion rate was 75.5%, and the mass yield of formic acid was 42.5%, the mass yield of methyl formate was 56.5%, the yield of methyl acetal was 19.5%, and the yield of formaldehyde was 10%.
[0064] The preparation of V-Beta nano molecular sieve catalyst is described in Example 1.
[0065] Example 12
[0066] In this example, 2g corn stalks and 22.5mL methanol were used as raw materials, 22.5mL water was used as solvent, 0.5g acid and 0.1g V-Beta nano molecular sieve were used as catalysts, placed in a high temperature and high pressure reactor with stirring, oxygen was charged to a pressure of 2MPa, stirred and reacted for 2h at 150℃, cooled to room temperature after the reaction, the product in the reactor was weighed, filtered and separated, the filter residue and filtrate were collected respectively, the filtrate was stored in a sealed bottle, the filter residue was dried and weighed, the filter residue was calcined, and the V-Beta nano molecular sieve catalyst was recovered. The results showed that the corn stalk conversion rate was 91.1%, and the mass yield of formic acid was 52%, the mass yield of methyl formate was 54%, the yield of methylal was 16%, and the yield of formaldehyde was 40.5% based on the initial stalk mass.
[0067] The preparation of V-Beta nano molecular sieve catalyst is described in Example 1.
[0068] Embodiment 13
[0069] In this example, 2g corn stalks and 22.5mL methanol were used as raw materials, 22.5mL water was used as solvent, 0.5g acid and 0.1g V-Beta nano molecular sieve were used as catalysts, placed in a high temperature and high pressure reactor with stirring, oxygen was charged to a pressure of 2MPa, stirred and reacted for 2h at 155℃, cooled to room temperature after the reaction, the product in the reactor was weighed, filtered and separated, the filter residue and filtrate were collected respectively, the filtrate was stored in a sealed bottle, the filter residue was dried and weighed, the filter residue was calcined, and the V-Beta nano molecular sieve catalyst was recovered. The results showed that the corn stalk conversion rate was 93.4%, and the mass yield of formic acid was 27.5%, the mass yield of methyl formate was 54%, the yield of methylal was 13.5%, and the yield of formaldehyde was 48.5% based on the initial stalk mass.
[0070] The preparation of V-Beta nano molecular sieve catalyst is described in Example 1.
[0071] Embodiment 14
[0072] In this example, 2g corn stalks and 22.5mL methanol were used as raw materials, 22.5mL water was used as solvent, 0.5g acid and 0.1g V-Beta nano molecular sieve were used as catalysts, placed in a high temperature and high pressure reactor with stirring, oxygen was charged to a pressure of 2MPa, stirred and reacted at 160℃ for 2h, cooled to room temperature after the reaction, the product in the reactor was weighed, filtered and separated, the filter residue and filtrate were collected respectively, the filtrate was stored in a sealed bottle, the filter residue was dried and weighed, the filter residue was calcined, and the V-Beta nano molecular sieve catalyst was recovered. The results showed that the corn stalk conversion rate was 77.8%, and the mass yield of formic acid was 21.3%, the mass yield of methyl formate was 46%, the yield of methylal was 9%, and the yield of formaldehyde was 13.5% based on the initial stalk mass.
[0073] The preparation of V-Beta nano molecular sieve catalyst is described in Example 1.
[0074] Embodiment 15
[0075] In this example, 2g corn cob and 22.5mL methanol were used as raw materials, 22.5mL water was used as solvent, 0.5g acid and 0.1g V-Beta nano molecular sieve catalyst were placed in a high temperature and high pressure reactor with stirring, oxygen was filled to a pressure of 2MPa, and the reaction was stirred at 130°C for 2h. After the reaction was completed, it was cooled to room temperature, the product in the reactor was weighed, and then filtered and separated, and the filter residue and filtrate were collected respectively. The filtrate was stored in a sealed bottle, the filter residue was dried and weighed, the filter residue was calcined, and the V-Beta nano molecular sieve catalyst was recovered. The results showed that the corn cob conversion rate was 82.6%, and the mass yield of formic acid was 45%, the mass yield of methyl formate was 59.6%, the yield of methylal was 20.2%, and the yield of formaldehyde was 14.4%.
[0076] The preparation of V-Beta nano molecular sieve catalyst is described in Example 1.
[0077] Example 16
[0078] In this example, 2g of poplar wood chips and 22.5mL of methanol were used as raw materials, 22.5mL of water was used as solvent, 0.5g of acid and 0.1g of V-Beta nano molecular sieve catalyst were placed in a high temperature and high pressure reactor with stirring, oxygen was filled to a pressure of 2MPa, and the reaction was stirred at 130°C for 2h. After the reaction was completed, it was cooled to room temperature, the product in the reactor was weighed, and then filtered and separated, and the filter residue and filtrate were collected respectively. The filtrate was stored in a sealed bottle, the filter residue was dried and weighed, the filter residue was calcined, and the V-Beta nano molecular sieve catalyst was recovered. The results showed that the sawdust conversion rate was 88.3%, and the mass yield of formic acid was 44%, the mass yield of methyl formate was 66.5%, the yield of methylal was 19.5%, and the yield of formaldehyde was 18.9% based on the mass of the initial sawdust.
[0079] The preparation of V-Beta nano molecular sieve catalyst is described in Example 1.
[0080] Embodiment 17
[0081] In this example, 2g bagasse and 22.5mL methanol were used as raw materials, 22.5mL water was used as solvent, 0.5g acid and 0.1g V-Beta nano molecular sieve catalyst were placed in a reactor, oxygen was charged at 2MPa, and the reaction was stirred at 130°C for 2h. After the reaction was completed, the product in the reactor was cooled to room temperature, and the mass was weighed, and then filtered and separated. The filter residue and filtrate were collected respectively, and the filtrate was stored in a sealed bottle. The filter residue was dried and weighed. The results showed that the conversion rate of bagasse was 86.6%. Based on the initial bagasse mass, the mass yield of formic acid was 47%, the mass yield of methyl formate was 58%, the yield of methylal was 14%, and the yield of formaldehyde was 18.5%.
[0082] The preparation of V-Beta nano molecular sieve catalyst is described in Example 1.
[0083] Embodiment 18
[0084] In this example, 2g bamboo and 22.5mL methanol were used as raw materials, 22.5mL water was used as solvent, 0.5g acid and 0.1g V-Beta nano molecular sieve catalyst were placed in a reactor, oxygen was charged at 2MPa, and the reaction was stirred at 130℃ for 2h. After the reaction was completed, the product in the reactor was cooled to room temperature, and the mass was weighed, and then filtered and separated. The filter residue and filtrate were collected respectively, and the filtrate was stored in a sealed bottle. The filter residue was dried and weighed. The results showed that the bamboo conversion rate was 80.8%, and the mass yield of formic acid was 45%, the mass yield of methyl formate was 57.8%, the yield of methylal was 16%, and the yield of formaldehyde was 13.2% based on the initial bamboo mass.
[0085] Embodiment 19
[0086] In this example, 2g of bean stalks and 22.5mL of methanol were used as raw materials, 22.5mL of water was used as solvent, 0.5g of acid and 0.1g of V-Beta nano molecular sieve catalyst were placed in a reactor, oxygen was charged at 2MPa, and the reaction was stirred at 130°C for 2h. After the reaction was completed, the product in the reactor was cooled to room temperature, and the mass was weighed, and then filtered and separated. The filter residue and filtrate were collected respectively, and the filtrate was stored in a sealed bottle. The filter residue was dried and weighed. The results showed that the conversion rate of bean stalks was 81.2%. Based on the initial bean stalk mass, the mass yield of formic acid was 44%, the mass yield of methyl formate was 58.0%, the yield of methylal was 17.2%, and the yield of formaldehyde was 12.8%.
[0087] The preparation of V-Beta nano molecular sieve catalyst is described in Example 1.
[0088] Embodiment 20
[0089] In this example, 2g corn stalks and 3mL methanol were used as raw materials, 42mL water was used as solvent, 0.5g acid and 0.1g V-Beta nano molecular sieve were used as catalysts, placed in a high temperature and high pressure reactor with stirring, oxygen was charged to a pressure of 2MPa, stirred and reacted at 130°C for 2h, cooled to room temperature after the reaction, the product in the reactor was weighed, filtered and separated, the filter residue and filtrate were collected respectively, the filtrate was stored in a sealed bottle, the filter residue was dried and weighed, the filter residue was calcined, and the V-Beta nano molecular sieve catalyst was recovered. The results showed that the corn stalk conversion rate was 82.4%, and the mass yield of formic acid was 88%, the mass yield of methyl formate was 18%, and the yield of acetic acid was 9% based on the initial stalk mass.
[0090] The preparation of V-Beta nano molecular sieve catalyst is described in Example 1.
[0091] Comparative Example 1
[0092] In this example, 2 g corn stalks were used as raw materials, 40 mL water was used as solvent, 0.5 g acid and 0.1 g H5PV2MoO 40 The catalyst was placed in a high-temperature and high-pressure reactor with stirring, and oxygen was filled to a pressure of 2MPa. The reaction was stirred at 130°C for 2h. After the reaction was completed, it was cooled to room temperature, and the product in the reactor was taken out and weighed. Then, it was filtered and separated, and the filter residue and filtrate were collected respectively. The filtrate was stored in a sealed bottle, the filter residue was dried and weighed, and the filter residue was calcined. The results showed that the corn straw conversion rate was 38.8%, and the formic acid mass yield was 29.8%, the methyl formate mass yield was 17.9%, the methylal yield was 6.1%, and the formaldehyde yield was 5.3%.
[0093] Comparative Example 2
[0094] In this example, 15 ml of methanol and 2 g of corn stalks were used as raw materials, 30 mL of water was used as solvent, 0.5 g of acid and 0.1 g of H5PV2MoO 40 The catalyst was placed in a high-temperature and high-pressure reactor with stirring, and oxygen was filled to a pressure of 2MPa. The reaction was stirred at 130°C for 2h. After the reaction was completed, it was cooled to room temperature, and the product in the reactor was taken out and weighed. Then, it was filtered and separated, and the filter residue and filtrate were collected respectively. The filtrate was stored in a sealed bottle, the filter residue was dried and weighed, and the filter residue was calcined. The results showed that the corn straw conversion rate was 57.6%, and the formic acid mass yield was 39%, the methyl formate mass yield was 19.8%, the methylal yield was 7.2%, and the formaldehyde yield was 6.4% based on the initial corn straw mass.
Claims
1. A method for preparing oxygen-containing chemicals by synergistic catalytic oxidation of lignocellulose and methanol, characterized in that: The method comprises the following specific steps: adding lignocellulose raw material, methanol, inorganic acid, V-Beta nano molecular sieve catalyst and water into a Hastelloy reaction kettle, filling with a certain pressure of O2 or high-pressure air, stirring and reacting at a certain temperature for a certain time, rapidly cooling to room temperature after the reaction is completed, filtering and separating, collecting reaction residue and filtrate respectively, the filtrate being the final product, calcining the residue, and recovering the V-Beta nano molecular sieve catalyst.
2. The method for preparing oxygen-containing chemicals by synergistic catalytic oxidation of lignocellulose and methanol according to claim 1, characterized in that: The specific preparation steps of the V-Beta nano molecular sieve catalyst are as follows: Step 1: Dissolve ammonium metavanadate in water and mix it evenly with white carbon black, and dry it at 60-80°C for 5-12 hours. The mass ratio is white carbon black: ammonium metavanadate: water = 1: 0.1-0.3: 0.8-1.2; Step 2: Mix aluminum oxide and tetraethylammonium hydroxide solution, stir magnetically for 30 minutes at a speed of 500 r / min, so that the aluminum oxide is completely dissolved, and the mass ratio of aluminum oxide to tetraethylammonium hydroxide solution is 1:20-50; Step 3: Add the dried white carbon black to the mixed solution, mix well, and dry at 70° C. for 6-8 hours to obtain a mixture, wherein the mass ratio of aluminum oxide to white carbon black is 1:25-50; Step 4: Grind the dried mixture in the above step 3 and transfer it into an open glass vessel, then transfer it into the lining of a hydrothermal reactor, add 4 to 20 mL of deionized water into the lining of the hydrothermal reactor, and prevent water outside the glass vessel from entering the glass vessel; adjust the hydrothermal reactor to 160 to 180° C. under steam-assisted conditions, and crystallize the mixture for 8 to 20 hours to obtain a crystalline product; Step 5: After the crystalline product is naturally cooled to room temperature, it is washed twice and dried, and calcined at 500-600° C. in an air atmosphere for 12 hours to obtain a V-Beta nanomolecular sieve catalyst with high crystallinity.
3. The method for preparing oxygen-containing chemicals by synergistic catalytic oxidation of lignocellulose and methanol according to claim 1, characterized in that: The types of lignocellulose raw materials include corn straw, wheat straw, bean straw, corn cob, sugarcane bagasse, wood chips and bamboo.
4. The method for preparing oxygen-containing chemicals by synergistic catalytic oxidation of lignocellulose and methanol according to claim 1, characterized in that: The inorganic acids used include phosphoric acid, hydrochloric acid, sulfuric acid, and nitric acid.
5. The method for preparing oxygen-containing chemicals by synergistic catalytic oxidation of lignocellulose and methanol according to claim 1, characterized in that: The mass ratio of lignocellulosic raw material to methanol is 1:1 to 1:
10.
6. The method for preparing oxygen-containing chemicals by synergistic catalytic oxidation of lignocellulose and methanol according to claim 1, characterized in that: The mass ratio of lignocellulose raw material to water is 1:5 to 1:
25.
7. The method for preparing oxygen-containing chemicals by synergistic catalytic oxidation of lignocellulose and methanol according to claim 1, characterized in that: The use ratio of inorganic acid and V-Beta nano molecular sieve catalyst is: the mass ratio of lignocellulose raw material to inorganic acid is 1:0.1 to 1:0.8, and the mass ratio of lignocellulose raw material to V-Beta nano molecular sieve catalyst is 1:0.02 to 1:0.
2.
8. The method for preparing oxygen-containing chemicals by synergistic catalytic oxidation of lignocellulose and methanol according to claim 1, characterized in that: The reaction parameters are: reaction temperature 100°C to 160°C, reaction time 0.5h to 3h, reaction pressure 1.0MPa to 5MPa.
Citation Information
Patent Citations
Method of preparing oxygen-containing chemicals by catalytic oxidation of biomass
CN106831367A
Method for preparing lactic acid from corncob under catalysis of molecular sieve based catalyst
CN108191632A
Preparation method of Sn-beta molecular sieve nanocrystal
CN110422857A
Method for preparing formic acid and formaldehyde through synergistic catalytic oxidation of biomass and methanol
CN115872851A
Cited By
Efficient methanol preparation method based on biomass graded catalytic conversion and cycle coupling
CN120518439A